KEBIJAKAN EKONOMI DAN PENINGKATAN DAYA SAING INDONESIA MENGHADAPI MASYARAKAT EKONOMI ASEAN 2015 - Suharyono Suharyono (Universitas Nasional, 2016)
Since 2003 Bali Concord II that sett up (ASEAN Economic Community/AEC, Indonesia has been engaged in the efforts of strengthening the country especially setting forth economic policy that is condusive to achieving the country’s level of competition. The paper shall deal with challenges that Indonesia has faced in the issue. The challenges that are identified include balance of trade, dependable entrepreneurs, and rate of productivity of manpower.How has the government come up with sound economic policies? The account finds that the most recent economic policies of Joko Widodo have not achieved better results in coping the cahallenges. Keywords : Economic policy, State, Competition, ASEAN Economic Community.